2020
DOI: 10.1037/adb0000556
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous alcohol and marijuana use in daily life: Implications for level of use, subjective intoxication, and positive and negative consequences.

Abstract: Simultaneous alcohol and marijuana (SAM) use is prevalent among young adult drinkers and associated with increased risk for harms. Less understood about SAM use is whether increased risk is incurred on SAM use occasions relative to occasions in which individuals used only 1 substance. From a sample of young adult SAM users, we compared occasions in which individuals simultaneously used alcohol and marijuana so that the effects overlapped (“SAM days”), occasions involving only alcohol (“alcohol days”), and occa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 28 publications
2
96
2
Order By: Relevance
“…23 A higher prevalence of simultaneous use of alcohol and marijuana use is the main cause of the increased risk of harm among adult alcohol users. 28,29 A similar result was also reported by O'Hara et al 30 indicating higher complementary use of cannabis use in US students taking consuming a higher amount of alcohol for social reasons. The result from Polish undergraduate students indicated higher odds of binge drinking among males, social sciences studying, living in a dorm or apartment, and living in an urban area.…”
Section: Introductionsupporting
confidence: 75%
“…23 A higher prevalence of simultaneous use of alcohol and marijuana use is the main cause of the increased risk of harm among adult alcohol users. 28,29 A similar result was also reported by O'Hara et al 30 indicating higher complementary use of cannabis use in US students taking consuming a higher amount of alcohol for social reasons. The result from Polish undergraduate students indicated higher odds of binge drinking among males, social sciences studying, living in a dorm or apartment, and living in an urban area.…”
Section: Introductionsupporting
confidence: 75%
“…First, with 62.3% of participants reporting past-year substance use beyond alcohol, marijuana, or tobacco use, SAM users might be likely to use other drugs such as opioids, club drugs, and stimulants. These findings are in line with other emerging evidence pointing to the high prevalence and potential for deleterious effects of the tri-use of alcohol, marijuana, and tobacco (Baggio et al 2014; Linden-Carmichael, Van Doren, et al, 2020; Roche et al, 2019) including several recent studies using person-centered statistical analyses (i.e., Bailey et al, 2019; Davis et al, 2019). In particular, Davis and colleagues found that individuals reporting simultaneous cannabis and tobacco use may be at highest risk for problematic outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Most (63%) reported living in a house/apartment/room that was not affiliated with the local university. Additional sample details are provided in the parent study [5].…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Relative to individuals who only use alcohol or who use both substances but not at the same time, individuals who engage in SAM use are at increased risk for heavy substance use and negative consequences such as physical health problems, driving under the influence, academic and occupational problems, and social consequences [2][3][4]. Recent daily diary work conducted in the USA has extended our knowledge beyond person-level differences that distinguish individuals who engage in SAM use from individuals who engage in only alcohol use by instead contrasting behavioural outcomes on days when they reported SAM use relative to days the same individual reported only alcohol use [5,6]. Though findings are mixed, one study supported that SAM use is linked with heavier alcohol use [6] and another study showed that SAM use is linked with negative consequences on the same day-most commonly blacking out, embarrassing one's self and negative physical effects even after controlling for number of drinks consumed, demonstrating the potential unique risks of SAM use on experiencing harms [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation